Novel First-Order Current-Mode All-Pass Sections Using CCIII - Sudhanshu Maheshwari; Iqbal A. Khan (Active and Passive Electronic Components)
Two new configurations realizing canonical first-order current-mode all-pass sections (APSs) using a single third generation current conveyor (CCIII) are given. Using each configuration, two types of first-order all-pass filters can be derived giving rise to four distinct circuits for APS, three of which are novel. Each APS employs only a single CCIII and a minimum of passive components: one resistor and one capacitor. The circuits are suited for MOS implementation. The SPICE simulation results for frequency response as well as transient response are incorporated to verify the theory.